Eslicarbazepine acetate for partial-onset seizures. (December 2011) - Rauchenzauner, Markus; Luef, Gerhard
Eslicarbazepine acetate (ESL), a new voltage-gated sodium channel blocker that is chemically related to carbamazepine and partially metabolized to oxcarbazepine, has attracted attention as results of previous Phase II and III studies demonstrated and confirmed efficacy and tolerability of ESL 800 and 1200 mg once daily as add-on therapy for adult patients with drug-resistant partial-onset seizures. In children, efficacy data point towards a dose-dependent decrease in seizure frequency and tolerability analyses showed a low incidence of mild drug-related adverse effects at 5 and 15 mg/kg/day. The most frequently reported adverse effects were dizziness, somnolence, headache, diplopia, nausea and vomiting. The convenience of once-daily dosing and a short/simple titration regimen in combination with a comparative efficacy and tolerability profile might promote ESL as a valid alternative to the current adjunctive antiepileptic drug therapy armamentarium for drug-resistant partial seizures in adults. Since clinical trials in children and adolescents on ESL efficacy and safety are ongoing and data already published are far from conclusive, the therapeutic value of ESL in this special population has to be established in the near future.